Factor a 2 bc + ab 2 c + abc 2.

Question

Asked 4/30/2015 11:16:13 AM

Updated 5/3/2015 12:52:49 PM

1 Answer/Comment

Flagged by janezeshun [5/3/2015 4:05:57 AM], Edited by jeifunk [5/3/2015 12:52:49 PM]

s

Question

Asked 4/30/2015 11:16:13 AM

Updated 5/3/2015 12:52:49 PM

1 Answer/Comment

Flagged by janezeshun [5/3/2015 4:05:57 AM], Edited by jeifunk [5/3/2015 12:52:49 PM]

Rating

8

a^2bc + ab^2c + abc^2

= abc(a + b + c)

= abc(a + b + c)

Added 5/3/2015 4:06:30 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/3/2015 12:52:45 PM]

Simplify R - [S + T]. User: Q = 7m + 3n, R = 11 - 2m, S = n + 5, and T = -m - 3n + 8.
Simplify R - [S + T].

Question

Updated 5/1/2015 2:23:25 AM

1 Answer/Comment

R-(S+T)

=11-2m-(n+5-m-3n+8)

=11-2m+2n+m-13

=-m+2n-2

=11-2m-(n+5-m-3n+8)

=11-2m+2n+m-13

=-m+2n-2

Added 5/1/2015 2:23:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/6/2015 12:17:12 PM]

Q = 7m + 3n, R = 11 - 2m, S = n + 5, and T = -m - 3n + 8.
Simplify R - [S + T].

Question

Updated 5/2/2015 8:52:56 PM

1 Answer/Comment

Q = 7m + 3n, R = 11 - 2m, S = n + 5, and T = -m - 3n + 8.

R - [S + T]

= 11 - 2m - (n + 5 - m - 3n + 8)

= 11 - 2m - (-2n - m + 13)

= 11 - 2m + 2n + m - 13

= -2 - m + 2n

R - [S + T]

= 11 - 2m - (n + 5 - m - 3n + 8)

= 11 - 2m - (-2n - m + 13)

= 11 - 2m + 2n + m - 13

= -2 - m + 2n

Added 5/2/2015 8:52:56 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/6/2015 12:20:45 PM]

Simplify (x - y + 1) - (x + y - 1)

Question

Updated 5/1/2015 2:17:01 AM

1 Answer/Comment

(x-y+1)-(x+y-1)

=x-y+1-x-y+1

=-2y+2

=x-y+1-x-y+1

=-2y+2

Added 5/1/2015 2:17:01 AM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [5/1/2015 4:45:01 AM]

34,864,929

questions answered

There are no comments.